2021
DOI: 10.5670/oceanog.2021.supplement.02-22
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Observing System for Monitoring Marine Debris and Biodiversity

Abstract: Wood, pumice, drifting kelp, and other natural marine debris have long played important roles in marine ecosystems. Today, oceanic "litter" generated by human activities, notably plastics, constitutes the majority of marine debris and is mostly harmful to those ecosystems. In the twentieth century, plastic became a symbol of technological development and globalization of the world's economy.Cheap, durable, and long-lasting, with a broad variety of properties that are attractive for an array of human uses, plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The influence of these uncertainties of the source on debris patterns is small in the garbage patches where debris items reside for a long time (e.g., [ 24 ]), during which they “forget” their origin. To simulate the garbage patch, a constant (in time and intensity) tracer input to the ocean was set up from all coastal grid points, and the model was looped between years 1992 and 2020 under a weak dissipation, representing degradation of debris due to physical factors (UV and storms) and biological interactions [ 25 , 26 ] until the model solution saturated to 95% (the root-mean-square difference between subsequent cycles). We used the 2 month mean concentration for July to August 2019 (the time period that most closely matched that of our observations) in subsequent analyses, to smooth out short-term fluctuations.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of these uncertainties of the source on debris patterns is small in the garbage patches where debris items reside for a long time (e.g., [ 24 ]), during which they “forget” their origin. To simulate the garbage patch, a constant (in time and intensity) tracer input to the ocean was set up from all coastal grid points, and the model was looped between years 1992 and 2020 under a weak dissipation, representing degradation of debris due to physical factors (UV and storms) and biological interactions [ 25 , 26 ] until the model solution saturated to 95% (the root-mean-square difference between subsequent cycles). We used the 2 month mean concentration for July to August 2019 (the time period that most closely matched that of our observations) in subsequent analyses, to smooth out short-term fluctuations.…”
Section: Methodsmentioning
confidence: 99%
“…If the Sargasso Sea is in fact only one of several neustonic seas, these other regions are worthy of future study and special consideration. Integration of observing systems of marine debris and biodiversity [41] would advance our understanding of the complex dynamics and multi-disciplinary interactions in the pelagic ocean. Ecological studies on the food webs and life history of neustonic species will allow us to better understand their temporal cycles and connectivity, and community science will help us better map life at the air-sea interface.…”
Section: Discussionmentioning
confidence: 99%
“…With plastic pollution waste generation and inputs to the ocean expected to exponentially increase over the next few decades 38,40 , a steady source of substrate may sustain the neopelagic as a persistent community. This research presents the cusp of discovery of neopelagic communities, and further innovative and interdisciplinary studies (including of trophodynamics and potential competitive interactions between pelagic and coastal species) are needed to more fully understand the role of floating plastics in ocean gyres 41 . Future research should also investigate the degree to which the patterns observed in the North Pacific Ocean occur in other ocean gyre systems.…”
Section: Articlementioning
confidence: 99%